Peningkatan Hasil Belajar Siswa Melalui Penerapan Model Problem Based Learning Materi Ekosistem di Sekolah Dasar - Sulfah Yulianti; ma’ruf; anisa (CV Edujavare Publishing, 2024)
This study aims to determine the improvement of science learning outcomes through the application of problem-based learning models in fifth-grade students of SD Negeri 123 Banti. The subjects in this study were 16 fifth-grade students of SD Negeri 123 Banti. This type of research is Classroom Action Research with Kurt Lewin which consists of four main steps, namely planning, implementation of actions, observation, and reflection. Data collection techniques used were learning outcome tests, student activity observation sheets, and documentation. While the data analysis techniques used quantitative and qualitative data analysis. The results of the study showed that in the first cycle that was completed individually from 16 students only 7 people or 43.7% met the minimum completeness criteria (KKM). Classically it has not been met because the average value obtained is 66.06. While in the second cycle where out of 16 students there are 14 people or 87.5% who met the minimum completeness criteria (KKM) and classically it has been met, namely the average value obtained is 86.43. Based on the research results above, it can be concluded that the science learning outcomes of fifth-grade students at SD Negeri 123 Banti, Baraka District, Enrekang Regency, through the implementation of the problem-based learning model have improved.